2014
DOI: 10.1055/s-0034-1383143
|View full text |Cite
|
Sign up to set email alerts
|

Antiglaukomatöse Filtrationschirurgie bei alten Glaukompatienten ab dem 80. Lebensjahr: Analyse der postoperativen Risiken

Abstract: The postoperative risks of antiglaucomatous filtering surgery did not increase with age or comorbidity. However, even minor perioperative complications had direct implications on the duration of the hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“… 53 However, this study only had a small number of cases that used subconjunctival LA, and this finding has not been replicated. Other studies have found no difference in outcome, when comparing subconjunctival LA and Ga 54 55 and subconjunctival vs Topical, 58 or subconjuctival vs retrobulbar (non-penetrating surgery). 56 A recent review article on ‘modern filtration surgery’ concluded that ‘subconjunctival anesthesia is safe’.…”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 92%
“… 53 However, this study only had a small number of cases that used subconjunctival LA, and this finding has not been replicated. Other studies have found no difference in outcome, when comparing subconjunctival LA and Ga 54 55 and subconjunctival vs Topical, 58 or subconjuctival vs retrobulbar (non-penetrating surgery). 56 A recent review article on ‘modern filtration surgery’ concluded that ‘subconjunctival anesthesia is safe’.…”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 92%